Immunohistochemical detection of pro-inflammatory and anti-inflammatory cytokines in granulomas in cattle with natural Mycobacterium bovis infection - Canal, Ana María (2017)
Cellular immune response was evaluated in lymph nodes and lung with different granulomatous lesions from cattle naturally infected with Mycobacterium bovis. For this purpose, we assessed pro-inflammatory and anti-inflammatory cytokines by immunohistochemical assays. Immunoreaction was observed for all the cytokines analyzed. Fourteen animals displayed advanced stage IV granulomas, with intense immunoreactivity to IFN-γ and TGF-β in areas of caseous necrosis, macrophages and lymphocytes. Seven animals showed stage III granuloma, with high immunoreactivity to IFN-γ (average of 44.5% immunoreactive cells) and moderate to TNF-αand to the anti-inflammatory cytokines IL-10 and TGF-β, in relation to the proliferation of fibroblasts in granuloma periphery We found satellite stage I granulomas in 4 bovines and stage II granulomas in 2 bovines, which exhibited low immunostaining response (‐13%). Cytokine expression in stage III and IV granulomas was significant, with predominance of immunoreactivity to IFN-γ, thus suggesting a strong, longstanding local immune response mediated by macrophages and epithelioid cells. In addition, these two stages displayed lower reactivity to IL-10; which suggests a deficit of anti-inflammatory cytokines, suppressed immunity and persistence of the infection. High expression of TGF-β could indicate a chronic processwith greater tissue damage and fibrosis. Numerous bacilli observed in necrotic areas in stage III and IV granulomas with low expression of IL-1β suggest failure in the immune response with bacterial multiplication. In this study, evidence of in situ presence of cytokines demonstrates these cytokines are involved in the development and evolution of bovine tuberculosis granulomas.